Pengaruh Penggunaan Video Pembelajaran Berbasis YouTube terhadap Minat Belajar Bahasa Inggris Siswa Kelas X SMA Negeri 1 Narmada - Ahmad Fauzan; Nurul Hidayati; Rizky Ananda Putra (Educational Note, 2026)
This research is motivated by the importance of innovating digital learning media to overcome students’ low motivation in foreign language learning. The study aims to determine the effect of using YouTube-based learning videos on the English learning interest of tenth-grade students at SMA Negeri 1 Narmada. The research method used is quantitative with a quasi-experimental design. The research sample was selected using the cluster random sampling technique and divided into an experimental group that received YouTube-based video learning treatment and a control group that used conventional methods. Learning interest data were collected through a structured questionnaire that had been tested for validity and reliability, and then analyzed using a t-test. The main findings of the study show a significant increase in the learning interest of the experimental class compared to the control class (p < 0.05) with a large effect size (Cohen’s d = 1.26). Interactive activities and content visualization in the learning videos proved effective in attracting students’ attention and increasing their classroom engagement. The conclusion of this study is that the use of YouTube-based learning videos has a significant positive effect on increasing students’ interest in learning English. This digital medium is recommended to be implemented as an alternative adaptive and interactive learning instrument at the secondary school level.